Hospital Admission for Symptoms Exacerbation in 2,075 Infants Suffering from Recurrent Asthma-Like Symptoms: (Eisl-3 South America) - Mallol-Villablanca, E; Aguirre-Camposano, V (Codon Publications, 2021)
Background: Contrary to what happens in children and adults, the prevalence and the factors related to hospitalisation for asthma/wheezing in infants with recurrent asthma-like symptoms are poorly known. Methods: This study is part of the International Study of Wheezing in infants Phase 3; 2,079 infants (aged 12–18 months) with recurrent asthma-like symptoms, from 11 South American centres, were studied to determine the prevalence and the associated factors for wheezing exacerbation admission. Descriptive statistics and multivariate logistic regression were employed for analysis. Results: The prevalence of admission for wheezing was 29.7% (95% CI 27.7–31.6) and was signifi-cantly associated to severe wheezing episodes (OR: 3.89; 95% CI: 2.93–5.18, p<0.001), physician-diagnosed asthma (OR: 1.79; 95% CI: 1.33–2.41, p<0.0001), use of inhaled corticosteroids (OR: 1.78; 95%CI: 1.38–2.29, p<0.0001), maternal tobacco smoking during pregnancy (OR: 1.69; 95% CI: 1.19–2.39, p = 0.003) and onset of wheezing in the first trimester of life (OR: 1.30; 95% CI: 1.02–1.66, p = 0.038). Breast feeding ≥4 months (OR: 0.72; 95% CI: 0.54–0.96, p = 0.004), maternal high educational level (>12 years) (OR: 0.66; 95% CI: 0.51–0.85, p = 0.001) and total monthly household income ≥US$ 3,000 (OR: 0.34; 95% CI: 0.18–0.67, p = 0.002), were protective factors. Conclusions: Infants with recurrent asthma-like symptoms have a high rate of admissions. Tobacco smoking in pregnancy, viral respiratory illness in the first trimester of life and severe progression were risks for admissions. Improving medical management to prevent severe exacerbations, prolonging the postnatal period at home longer than 3 months, favouring breast-feeding and avoiding smoking during pregnancy may have a preventive role for admissions in infants with recurrent asthma-like symptoms. Copyright: Mallol J, et al. License: This open access article is licensed under Creative Commons Attribution 4.0 International (CC BY 4.0)